Dosis respuesta en la actividad analgésica periférica de la metformina en la prueba de contorsiones abdominales en ratones - Lujan-Carpio, E. (2018)
Objective: To evaluate the dose-response analgesic effect of metformin in an acute pain event in rodents. Materials and methods: Eighty (80) mice were used. The analgesic effect was evaluated using the abdominal writhing test in mice. Eight (8) groups of 10 mice each were formed: one diclofenac 8 mg/kg group, one tramadol group, one target group, and five experimental groups of metformin at doses of 50, 100, 150, 200 and 250 mg/kg. For the statistical analysis, the D'Agostino-Pearson test, one-tailed ANOVA test, Tukey's test, and Pearson's correlation coefficient were used. Results: The D'Agostino-Pearson normality test revealed a p-value < 0.05 in all groups. The ANOVA test showed a p-value < 0.0001. The Tukey's range test obtained a p-value < 0.05 between the target group and metformin groups at all doses, and between the diclofenac group and metformin groups at doses of 100, 150, 200 and 250 mg/kg, and a p-value > 0.05 between the tramadol group and metformin groups at doses of 100, 150, 200 and 250 mg/kg. The Pearson's correlation coefficient was r = -0.6897 and R = 0.4756, and yielded a p-value < 0.0001. Metformin showed a pain inhibition percentage in the range of 34.89 % to 92.62 %. Conclusions: It has been demonstrated that metformin at doses of 100, 150, 200 and 250 mg/kg had an acute analgesic effect in the abdominal writhing test in mice, with the 250 mg/kg dose being the one that showed the best effect. In addition, a dose-response effect was obtained in escalated doses of metformin.